Proton transfer reactions of N‐aryl triazolium salts: unusual ortho‐substituent effects1. (7th December 2014) - Tucker, David E.; Quinn, Peter; Massey, Richard S.; Collett, Christopher J.; Jasiewicz, David J.; Bramley, Christopher R.; Smith, Andrew D.; O'Donoghue, AnnMarie C.; Moss, R. A.; Gudmundsdottir, A.
<x xml:space="preserve">Abstract</x> Previous studies of the C(3)‐hydrogen/deuterium exchange reactions of the triazolium ion conjugate acids of triazolyl N‐heterocyclic carbenes revealed a change of mechanism under acidic conditions with N1‐protonation to a dicationic salt. Interestingly, the data suggested an increase in pKaN1 in the presence of a N‐pentafluorophenyl substituent relative to other N‐aryl substituents with hydrogens or methyl substituents rather than fluorines at the ortho‐positions. To probe the presence of an apparent donor effect of a N‐pentafluorophenyl substituent, which differs from the more common electron withdrawing effect of this group, we have studied the analogous deuterium exchange reactions of four triazolium salts with heteroatoms or heteroatom substituents in the 2‐position and/or 6‐position of the N‐aryl ring. These include triazolium salts with N‐2, 4, 6‐tribromophenyl 11, N‐2, 6‐dichlorophenyl 12, N‐2‐pyridyl 13 and N‐2‐pyrimidinyl 14 substituents. The log kex – pD profiles for 11, 12 and 14 were found to show similar trends at lower pDs as for the previously studied N‐pentafluorophenyl triazolium salt, hence supporting the presence an apparent donor effect on pKaN1. Surprisingly, the log kex – pD profile for N‐pyridyl salt 13 uniquely showed acid catalysis at lower pDs. We propose herein that this data is best explained by invoking an intramolecular general base role for the N‐(2‐pyridyl) substituent in conjunction with N1‐protonation on the triazolium ring. Finally, the second order rate constants for deuteroxide ion catalysed C(3)‐H/D exchange (kDO, M−1 s−1), which could be obtained from data at pDs >1.5, were used to provide estimates of C(3)‐carbon acid pKaC3 values for the four triazolium salts 11, 12, 13, 14. Copyright © 2014 John Wiley & Sons, Ltd.